A TRANSPARÊNCIA E O CONTROLE SOCIAL DOS GASTOS PÚBLICOS MUNICIPAIS - Maria Hescher Brizola, Evelyn; Fochesatto da Silva, Isabel; de Souza, Diana; José de Vargas, Alzenir (Revista Educação, Direito e Sociedade, 2021)
-